Molecular Mechanisms of the Teratogenic Effects of Thalidomide - Tomoko Asatsuma-Okumura; Takumi Ito; Hiroshi Handa (MDPI AG, 2020)
Thalidomide was sold worldwide as a sedative over 60 years ago, but it was quickly withdrawn from the market due to its teratogenic effects. Thalidomide was later found to have therapeutic effects in several diseases, although the molecular mechanisms remained unclear. The discovery of cereblon (CRBN), the direct target of thalidomide, a decade ago greatly improved our understanding of its mechanism of action. Accumulating evidence has shown that CRBN functions as a substrate of Cullin RING E3 ligase (CRL4CRBN), whose specificity is controlled by ligands such as thalidomide. For example, lenalidomide and pomalidomide, well-known thalidomide derivatives, degrade the neosubstrates Ikaros and Aiolos, resulting in anti-proliferative effects in multiple myeloma. Recently, novel CRBN-binding drugs have been developed. However, for the safe handling of thalidomide and its derivatives, a greater understanding of the mechanisms of its adverse effects is required. The teratogenic effects of thalidomide occur in multiple tissues in the developing fetus and vary in phenotype, making it difficult to clarify this issue. Recently, several CRBN neosubstrates (e.g., SALL4 (Spalt Like Transcription Factor 4) and p63 (Tumor Protein P63)) have been identified as candidate mediators of thalidomide teratogenicity. In this review, we describe the current understanding of molecular mechanisms of thalidomide, particularly in the context of its teratogenicity.